Diagnosis and endovascular treatment of iliac venous compression syndrome. (February 2019) - Sang, Hong-fei; Li, Jia-hong; Du, Xiao-long; Li, Weng-dong; Lei, Feng-rui; Yu, Xiao-bin; Zhu, Li-wei; Li, Cheng-long; Li, Xiao-qiang
Objectives: To report*The first two authors contributed equally to this work. our clinical experience on diagnostic criteria and endovascular management in patients with iliac venous compression syndrome. Method: Between July 2013 and May 2015, 85 consecutive patients with suspected iliac venous compression syndrome were evaluated by transfemoral venography and intravascular ultrasonography. Venographic evidence of iliac venous occlusion, stenosis, or pelvic collateral vessels, and the degree of stenosis as examined with intravascular ultrasonography were recorded. The endovascular procedure, complications, clinical outcome, and the Venous Clinical Severity Score were evaluated before and after the intervention. Results: Of the 85 limbs, 66 cases of iliac venous compression syndrome were confirmed and 19 cases were excluded. In all of the 66 patients, we successfully performed endovascular intervention (22 balloon dilations, 44 balloon dilations + stenting). Two patients with stent implantation developed acute lower extremity deep vein thrombosis, resulted in successful lysis of the thrombus with catheter-directed thrombolysis. Conclusions: The presence of intraluminal spurs and pelvic collateral vessels represents not only pathological and anatomical changes by long-term mechanical compression, but also indicators of the severity of iliac venous compression syndrome. The degree of stenosis cannot accurately represent the severity and treatment of iliac venous compression syndrome, especially in the right iliac vein. Endovascular intervention is a safe and effective treatment that reduces lower extremity symptoms. Full and intentional dilation of the intraluminal spurs is an important technical aspect, which is often ignored.